Synthesis and Characterization of Molecularly Imprinted Polymer for the Removal of Melamine from Milk, River Water and Human Blood Serum - Rachel Marcella, Roland (Universiti Malaysia Sarawak (UNIMAS), 2019)
Melamine (MEL) is a multipurpose compound which is capable to produce numerous useful products, however, MEL exploitation in many industries brought adverse effects to both mankind and environment. Molecular imprinting technology (MIT) is one of the methods that can be employed to solve problems regarding to MEL exploitation. MIT produce robust polymers called as molecularly imprinted polymers (MIPs) which can be applied to remove MEL from milk, river water and human blood serum. MIPs of MEL were synthesized using the non – covalent molecular imprinting method via precipitation polymerization (PP) and microemulsion polymerization (MP). In this research, MEL as a template molecule and 2,2’–azobisisobutyronitrile (AIBN) as an initiator were used in both polymerization methods. For PP, acrylamide (AAm), a functional monomer and divinylbenzene (DVB), a cross–linker, were dissolved in the mixture of dimethyl sulfoxide (DMSO) and acetonitrile (ACN). Meanwhile, for MP, acrylic acid (AA) acts as a functional monomer and N,N’–methylenebis(acrylamide) (MBAm) as a cross–linker, were dissolved in microemulsion solution. All MIPs and non–imprinted polymers (NIPs) were characterized by Fourier Transform Infra–Red spectroscopy (FT–IR), Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM) and Brunauer–Emmett–Teller (BET) analyzer. The thermal study of imprinted polymers was conducted using thermogravimetric analysis (TGA). The adsorption studies of the polymers were observed at 240 nm by using Reversed–Phase High Performance Liquid Chromatography (RP–HPLC). MIP 3 (PP) exhibited the highest rebinding efficiency which was 56.41% while NIP (PP) had lowest rebinding efficiency which was 16.31%. Similarly, MIP (MP) had attained higher rebinding efficiency of 61.98% than that NIP (MP) of 20.23%. Other adsorption studies including adsorbent dosages of polymer, initial concentrations and pH of melamine solution were successfully conducted on polymers synthesized by both polymerization methods. The results showed that both of the MIPs synthesized by PP and MP performed their highest adsorption efficiency in condition of 0.5 g of polymer, 25 ppm MEL solution and at neutral condition of pH 7 of 89.53% and 90.80%, respectively. For selectivity test, the relative selectivity coefficient of MEL and 2,4,6–trichlorophenol (2,4,6–TCP), a competitive molecule on MIPs and NIPs by PP and MP were 1.66 and 1.83, respectively. The removal efficiency of MEL by MIP 3 (PP) in milk (81.97%), river water (91.52%) and human blood serum (90.66%) were much higher than by NIP (PP). Likewise, the MIP (MP) had higher removal efficiency of MEL in milk, river water and human blood serum which were 84.30%, 94.26% and 93.32%, respectively as compared to NIP (MP). Therefore, the highest removal efficiencies of MEL are successfully attained by the imprinted polymers with molar ratio of 0.5 mol of MEL, the template molecule, 3.0 mol of functional monomer and 20.0 mol of cross linker.